Clinical indications for image-guided interventional procedures in the musculoskeletal system: a Delphi-based consensus paper from the European Society of Musculoskeletal Radiology (ESSR)-part VI, foot and ankle - Sconfienza, Luca Maria; Adriaensen, Miraude; Albano, Domenico; Alcala-Galiano, Andrea; Allen, Georgina; Aparisi Gómez, Maria Pilar; Aringhieri, Giacomo; Bazzocchi, Alberto; Beggs, Ian; Chianca, Vito; Corazza, Angelo; Dalili, Danoob; et al. (Springer Science and Business Media LLC, 2022)
Clarity regarding accuracy and effectiveness for interventional procedures around the foot and ankle is lacking. Consequently, a board of 53 members of the Ultrasound and Interventional Subcommittees of the European Society of Musculoskeletal Radiology (ESSR) reviewed the published literature to evaluate the evidence on image-guided musculoskeletal interventional procedures around this anatomical region.
Keywords: Interventional radiology; Ultrasonograph; Ankle; Foot; Achilles tendon